Development of Interactive Multimedia Learning Materials based on National Income for High School Students - Kurniasandi, Zordi; H Matsum, Junaidi; Warneri, Warneri; Wulandari, Novia Dian Kartika (Universitas Tanjungpura, 2024)
The developed interactive PowerPoint media utilizes hyperlink features, thus making the learning process more interactive. The PowerPoint media produced represents an innovative product derived from previously used media at SMAN 2 Sukadana Kayongutara. The aim of this study is to determine the feasibility of interactive PowerPoint media. The research stages include the preparation of interactive PowerPoint media, validation testing of the interactive PowerPoint media, and refinement of the interactive PowerPoint according to the suggestions provided by two validators. The aspects assessed in this research are content, media, and language. The feasibility of the interactive PowerPoint media was analyzed using the Gregory formula. The validation results indicate that each aspect